Developing RobEVELOPING DURABLE SUPERAMPHIPHOBIC COATING ON ROUGH ALUMINUM USING RESIDUAL FROM BURNED RECYCLED SILICONE RUBBER FOR ANTI-CORROSIONust Superamphiphobic Coating on Rough Aluminum Substrates Using Recycled Silicon Rubber and Simple Spray Pyrolysis Technique for Anticorrosion Applications - Choli, Gulista T.; Saifaldeenb, Zubayda S. (Science Journal of University of Zakho, 2023)
This study presents a new, cost-effective, and environmentally friendly approach for creating a superamphiphobic coating. The method involves using a spray coating technique to apply silicone rubber onto smooth and micro-rough aluminum (Al) substrates. To enhance the coating's surface energy reduction, a thin layer of silicone rubber – trifluorotoluene (SR-TFT) was added. The morphology and chemistry of the coatings were analyzed utilizing scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), atomic force microscopy (AFM), and Fourier Transform Infrared Spectrometer (FTIR). The coatings displayed superamphiphobic properties with contact angles (CAs) of 170° for water and over 150° for both glycerol and ethylene glycol. Additionally, a remarkably low water droplet sliding angle (SA) of less than 2° was observed for surfaces coated with silicone rubber (SR)- trifluorotoluene (TFT), whether smooth or roughened. The coatings were tested for mechanical and chemical durability by impinging water droplets and immersing them in an acidic liquid respectively. The results showed that SR-TFT-coated silicone rubber on micro-rough Al substrates maintained its superamphiphobic property and exhibited excellent corrosion resistance compared to hydrophilic Al plates. Furthermore, the coatings displayed self-cleaning properties when water droplets were poured over a dusty surface, as the rolling water droplets effectively collected contaminant particles, leaving the surface of the sample clean. These findings indicate potential applications for the developed coatings as self-cleaning surfaces in challenging environmental conditions.